Crowdsourcing Software Development - a possible path? - Candria, Denise de Campos; Araujo, Renata Mendes de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Crowdsourcing software development (CSSD) is a form of collective intelligence that is gaining attention in the Information Technology industry as a work alternative for software projects. CSSD represents a paradigm shift in the in-house development approach, promising deliveries with quality, productivity and innovation. Problem: CSSD is an emerging approach, both in research and in practice. Despite the existence of commercial supporting platforms, organizations of different sizes still face the challenge of how to organize the collective work, and a clear definition of how to perform CSSD is not known yet. Solution: This article presents an analysis of the literature to identify the main processes, practices, tools and platforms used in CSSD initiatives, and to understand the benefits and challenges reported in these initiatives as well. IS theory: Not applicable. Method: Descriptive research based on systematic literature mapping. Summary of Results: CSSD is understood as a democratic alternative with great potential for improving quality, productivity and innovation in software projects. However, challenges for its realization are many and of different kinds (technical, managerial, methodological and legal). Results also show not a large amount of CSSD case study reports in real situations. Contributions and Impact on the IS area: This work provides an overview of CSSD application, as well as a critical analysis of its advantages and challenges, contributing with discussions to the challenge of Information Systems and the Open World. This overview enables reflection on the adoption of CSSD, stimulating the research of solutions under development by crowds for companies of different sizes.